Using theory from the Global South: From social cohesion and collective efficacy to ubuntu - Dixon, Bill (Theoretical criminology, 2024)
Criminologists adopting a southern or decolonial perspective bemoan the failure to use theories from the Global South in making sense of crime and responses to it. This article takes the African philosophy and ethics of ubuntu and demonstrates how they might be used to ground a more relevant and effective approach to preventing urban violence in South Africa than northern ideas about social cohesion and collective efficacy current in dominant policy discourses. It argues that using indigenous bodies of knowledge like ubuntu can contribute not just to making good some of the damage done by colonial epistemicides but may also offer workable solutions to contemporary social problems in and beyond the Global South.